Subgroups of borderline personality disorder: A latent class analysis. (May 2023) - Antoine, Silvia M.; Fredborg, Beverley K.; Streiner, David; Guimond, Tim; Dixon-Gordon, Katherine L.; Chapman, Alexander L.; Kuo, Janice; Links, Paul; McMain, Shelley
Highlights: Three symptom subgroups of self-harming individuals with borderline personality disorder (BPD) were elucidated. Non-labile type demonstrates affective stability and few dissociative symptoms. Dissociative/paranoid type is characterized by dissociation, paranoia, lack of abandonment fears and lack of identity disturbance. Interpersonally unstable type fears abandonment and demonstrates interpersonal aggression. BPD subtyping may be helpful in determining initial treatment targets. Abstract: Borderline personality disorder (BPD) is characterized by instability in interpersonal, affective, cognitive, self-identity, and behavioral domains. For a BPD diagnosis, individuals must present at least five of nine symptoms, resulting in 256 possible symptom combinations; thus, individuals diagnosed with BPD can differ substantially. Specific symptoms of BPD tend to co-occur, suggesting BPD subgroups. To explore this potential, we analyzed data from 504 participants diagnosed with BPD enrolled in one of three randomized controlled trials conducted at center for Addiction and Mental Health in Toronto, Canada from 2002 to 2018. An exploratory latent class analysis (LCA) was conducted to identify symptom subgroups of BPD. Analyses indicated three latent subgroups. The first group ( n  = 53) is distinguished by a lack of affective instability and low levels of dissociative symptoms ( non-labile type ). The second group ( n  = 279) is characterized by high levels of dissociative and paranoid symptoms but low abandonment fears and identity disturbance ( dissociative/paranoid type ). The third group ( n  = 172) is characterized by high efforts to avoid abandonment and interpersonal aggression ( interpersonally unstable type ). Homogenous symptom subgroups of BPD symptoms exist and may have important implications for how to refine BPD treatment interventions.